The Use of Self-Information and Environment in Counseling Process - Muhammad Fatchurahman (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Counseling as one of the forms and techniques of assistance provided by schools in the context of implementing overall guidance, this is given to help students in their efforts to solve all problems. The availability of this information makes it easy for students to obtain the information needed for example to implement a decision, want to know about something both in terms of themselves and their environment. The use of self and environmental information in the counseling process occurs in the creation of rapport, in exploring, discovering the real problem, exploring and studying alternative problem solving, decision making, implementation of decisions taken and in evaluation and follow-up. Therefore the information used must meet the requirements: that is, careful and not prejudiced, up to date, comprehensive and available information sources. In addition to the above conditions, the principles of time saving, non-authoritarian and feedback are also taken into account, so that this can cause self and environmental information in the counseling process to be very important material for both the counselor and the client.